A comparative evaluation of changes in facial parameters in partial secondary adentia - Ibragimova F.I.; Qurbonov D.F (Research Parks Publishers, 2021)
Anthropometric methods are methods in which on the basis of which the continuity of the three sections of the face lies the pirincipus. They were invited by the circus